Sphingosine‐1‐Phosphate, Motor Severity, and Progression in Parkinson's Disease (MARK‐PD). Issue 9 (19th May 2021) - Schwedhelm, Edzard; Englisch, Catrin; Niemann, Louisa; Lezius, Susanne; von Lucadou, Mirjam; Marmann, Kristina; Böger, Rainer; Peine, Sven; Daum, Günter; Gerloff, Christian; Choe, Chi‐un
ABSTRACT: Background: Treatment with sphingosine‐1‐phosphate (S1P) agonists confers neuroprotective effects in animal models of Parkinson's disease (PD). Objectives: We assessed the association of serum S1P levels with motor and cognitive symptoms in patients with PD. Methods: S1P concentrations were analyzed with liquid chromatography–tandem mass spectrometry (LC–MS/MS) in serum of 196 PD patients and in 196 age‐ and sex‐matched controls. Motor (Unified Parkinson's disease rating scale III [UPDRS III], Hoehn and Yahr) and cognitive (Montreal Cognitive Assessment [MoCA]) function were assessed at baseline. Follow‐up data was available from 64 patients (median [interquartile range], 513 [381–677] days). Results: S1P levels were lower in PD patients compared with controls, that is 1.75 (1.38–2.07) and 1.90 (1.59–2.18) μmol/L, respectively ( P  = 0.001). In PD patients, lower S1P concentrations were associated with higher UPDRS III scores and Hoehn and Yahr stage. In the follow‐up cohort, S1P concentrations below the median were associated with faster motor decline (hazard ratio: 4.78 [95% CI, 1.98, 11.50]), but not with cognitive worsening. Conclusions: Our observations reveal an association of S1P with PD. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society